Phylogenomics Reveals an Ancient Hybrid Origin of the Persian Walnut. (4th June 2019) - Zhang, Bo-Wen; Xu, Lin-Lin; Li, Nan; Yan, Peng-Cheng; Jiang, Xin-Hua; Woeste, Keith E; Lin, Kui; Renner, Susanne S; Zhang, Da-Yong; Bai, Wei-Ning
Abstract: Persian walnut ( Juglans regia ) is cultivated worldwide for its high-quality wood and nuts, but its origin has remained mysterious because in phylogenies it occupies an unresolved position between American black walnuts and Asian butternuts. Equally unclear is the origin of the only American butternut, J. cinerea . We resequenced the whole genome of 80 individuals from 19 of the 22 species of Juglans and assembled the genome of its relatives Pterocarya stenoptera and Platycarya strobilacea . Using phylogenetic-network analysis of single-copy nuclear genes, genome-wide site pattern probabilities, and Approximate Bayesian Computation, we discovered that J. regia (and its landrace J. sigillata ) arose as a hybrid between the American and the Asian lineages and that J. cinerea resulted from massive introgression from an immigrating Asian butternut into the genome of an American black walnut. Approximate Bayesian Computation modeling placed the hybrid origin in the late Pliocene, ∼3.45 My, with both parental lineages since having gone extinct in Europe.